Bilateral compressive optic neuropathy secondary to tuberculum sella meningioma in pregnancy - Ainal Adlin N; Mushawiahti Mustapha; Amin Ahem; Safinaz Mohd Khialdin (Faculty of Medicine, Universiti Kebangsaan Malaysia Medical Centre, 2016)
A 37-year-old primigravida in her second trimester presented with bilateral painless progressive visual loss. Her vision was hand motion in both eyes. Both pupils were dilated with sluggish reaction to light. Both fundus appeared myopic with bilateral optic atrophy. Magnetic resonance imaging (MRI) of the brain revealed a suprasellar mass with optic chiasm compression and bilateral optic nerve atrophy. As the mass has compromised her vision, a semi-emergency craniotomy and excision of tumour was performed. Histopathological examination confirmed the diagnosis of low grade meningothelial meningioma. Both mother and foetus were well after the surgery. However, post-operatively her vision remained poor due to optic nerve atrophy.